Inclusive pre-laboratory learning in engineering laboratories: A systematic literature review on accessibility for students with disabilities - Kadek Adi Mahendra (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: Laboratory-based engineering education continues to face persistent challenges in ensuring accessible and inclusive learning environments for students with disabilities, particularly during the pre-laboratory phase, which is often characterized by technical complexity and safety risks. Inadequate pre-laboratory preparation may lead to learning barriers, reduced participation, and increased procedural errors. This study aims to systematically examine inclusive pre-laboratory learning strategies in engineering laboratories and analyze their implications for accessibility, laboratory safety, and overall learning quality. Methods: This study employed a systematic literature review grounded in inclusive education theory and Universal Design for Learning. Peer-reviewed scholarly articles related to engineering laboratories, pre-laboratory instruction, accessibility, and disability were systematically identified and thematically analyzed to explore dominant instructional approaches, design strategies, and reported educational outcomes. Findings: The review reveals that inclusive pre-laboratory learning, implemented through multimodal instructional materials, adaptive safety guidance, and virtual or simulated laboratory environments, consistently enhances students’ cognitive and procedural preparedness. These strategies reduce procedural errors, improve compliance with safety standards, and strengthen confidence and perceived safety among students with disabilities. The findings further demonstrate that such approaches benefit not only students with disabilities but also the broader student population, supporting the principles of Universal Design for Learning that emphasize flexibility, multiple means of representation, and learner engagement. Conclusion: Inclusive pre-laboratory learning is identified as an effective, scalable, and sustainable pedagogical strategy for developing equitable engineering laboratory environments without requiring extensive physical infrastructure modifications. Novelty/Originality of this article: This article contributes to the field by providing a systematic synthesis that integrates accessibility, laboratory safety, and pre-laboratory learning into a unified and practical conceptual framework, thereby advancing the state of the art in inclusive engineering education.